Seed degeneration of banana planting materials: strategies for improved farmer access to healthy seed - Jacobsen, K.; Omondi, Bonaventure Aman Oduor; Almekinders, Conny J.M.; Álvarez, E.; Blomme, Guy; Dita, M.; Iskra Caruana, M.L.; Ocimati, W.; Tinzaara, William; Kumar, P. Lava; Staver, Charles (Wiley, 2019)
Vegetatively propagated crops, suffer from yield loss and reduced stand density and longevity caused by the buildup of certain pests and pathogens between successive plantings via via infected planting material. We reviewed six seed‐borne phytosanitary problems to evaluate whether a seed degeneration framework is a useful tool to identify approaches to achieve healthier planting materials. Phytoparasitic nematodes and weevils generate gradual declines in yields and in sucker health. Fusarium wilt and Banana Bunchy top Virus cause progressive mat collapse across the field. Asymptomatic suckers from any mat in infested fields represent a risk to transmit the disease to a new field. Xanthomonas and Ralstonia wilts, due to incomplete systemicity, are intermediate in their threat to yield loss and frequency of transmission in suckers. Losses to banana streak virus are triggered by abiotic stress, although sucker transmission of episomal BSV also contributes. Our qualitative equation for seed degeneration covers a cycle beginning with the quality and risk factors of the planting material used to plant a new field and ends with the quality and risk factors of the suckers extracted from the field to plant a new field. Our review of five planting material multiplication methods commonly used in banana contrasts their differing usefulness to address seed degeneration in the small farm context. We propose that initiatives to offset banana seed degeneration should integrate the role of off‐farm actors into decentralized initiatives rather than attempt to duplicate national seed certification frameworks from other true seed or vegetatively propagated crops.